Cerebrovascular Atlas From MRA Imaging of 1336 Subjects - Xinyu, Wang; Liu, Jialu; Lou, Xiaoping (Image Analysis and Stereology, 2025)
This study aimed to create a comprehensive statistical atlas of cerebral arteries to accurately capture variations among individuals and across different age groups. We utilized 1,336 publicly available multicenter magnetic resonance angiography (MRA) and T1-weighted MRI datasets, employing an automated blood vessel segmentation method, FFCM-MRF, to segment all blood vessels and measure their radii. Subsequently, the binary segmentation and vascular radius images were nonlinearly registered to the Montreal Neurological Institute (MNI) brain template using the T1-weighted MRI dataset. This process resulted in the creation of atlases that illustrate the probability of arterial occurrence, the average arterial radius, and the standard deviation of the arterial radius. The constructed vascular statistical atlas effectively showcases the major arteries and, when integrated with the probability atlas and the average vessel radius atlas, indicates a significantly higher probability of larger arteries, which decreases as the vessel radius diminishes. This observation aligns with previous research findings, and the similarity between the probability atlas and individual vascular images reached as high as 0.9659. In conclusion, this atlas effectively covers arterial radius information across nearly the entire age range, enabling the identification of variations between individual arterial voxel radii and the population using this atlas, thereby providing an important reference for cerebral vascular research.